"What are my options?": How to have a goals-of-care conversation. Issue 7 (July 2022) - Bartholomew, Melissa Boettger
Abstract: Patients may choose to have a conversation with their providers about their care options. This article presents a guide for NPs for these goals-of-care conversations. NPs having these conversations can follow the strategies presented to plan the discussion, overcome barriers, and offer useful resources and support. Abstract : Patients may choose to have a conversation with their providers about their care options. This article presents a guide for NPs for these goals-of-care conversations. NPs having these conversations can follow the strategies presented to plan the discussion, overcome barriers, and offer useful resources and support.